From Professional Development to Educational ‎Transformation: Evaluating the Mobilizer Teacher Program ‎through Kirkpatrick’s Four-Level Model - Yusuf Pratama; Baso Intang Sappaile; Syahrul Syahrul; Hasriana Hasriana (JPI: Jurnal Pustaka Indonesia, 2025)
Indonesia’s Teacher Mobilizer Education Program (Program Pendidikan Guru Penggerak/PPGP) was designed to strengthen instructional leadership and accelerate school transformation, yet evidence of its outcomes across Kirkpatrick’s Four-Level Evaluation Model remains limited in Eastern Indonesia. This study evaluated reaction, learning, behavior, and results among PPGP participants in four public senior high schools in Makassar City. A qualitative evaluation design involved 16 purposively selected informants: Teacher Mobilizers, principals, peer teachers, and students. Data were generated through semi-structured interviews and document analysis of learning portfolios, mentoring reports, reflective journals, and school development documents. Data were analyzed using the Miles and Huberman interactive model and thematic coding based on the four Kirkpatrick levels. Credibility was supported through triangulation, member checking, and documentary verification. Participants reported positive reactions to the relevance of program content, facilitator support, mentoring, and collaborative learning. The program strengthened pedagogical knowledge, differentiated instruction, coaching, reflective practice, and instructional leadership. Behavioral outcomes included more student-centered teaching, restorative classroom management, peer collaboration, and active participation in school-improvement initiatives. At the organizational level, the program supported stronger professional learning communities, improved teacher collaboration, and greater student engagement. These findings indicate that PPGP can facilitate the transfer of professional learning into classroom and school-level practice. However, the qualitative design and limited number of schools constrain generalizability. Longitudinal mixed-method research is needed to assess sustained effects on teacher performance and student learning outcomes.